Belajar Demokratisasi Diri dan Demokratisasi Dalam Struktur - Sukarno, Bedjo - (UNIVERSITAS SLAMET RIYADI, 2011)
AbstractDemocracy gives complete freedom to every individual to realize himself and to actual Â all human potentials and talents become aware of his identity intact. democracy gives progress, convenience, besides that it also gives effect changes such as political crises, shock, dissatisfaction, annoyance. Democracy also carries consequences beyond the personal democratization and democratization of political structures.Key words: democratization, identity, political structures.